Development of sleep educational booklet for children with Autism Spectrum Disorder (Research, Society and Development, 2022)
Purpose: to develop educational booklets for guidance on sleep hygiene in children with Autism Spectrum Disorder (ASD). Methods: Materials were made through instructional design development stages: the first stage, Analysis and Planning, to optimize the assessment of sleep hygiene effectiveness; Second stage, Modeling, to prepare all the content used and the third stage, Implementation, in order to develop didactic resources, easy to understand. Strategies were carried out to improve children’s sleep quality, with instructions for parents and children. Results: six booklets were created for parents, four folders containing activities and two booklets containing stories for children with strategies that teach parents to apply sleep hygiene, as well as children to collaborate with the new routine. Conclusion: The present work enabled the development of educational materials, in the form of folders and booklets, providing information about sleep and sleep hygiene for children with ASD. The materials were based on scientific content, reinforcing the importance of application with the target audience and verification of its effectiveness.